Implementation of nave bayes algorithm for routing recommendations in software defined network (sdn) simulation - Yuggo Afrianto; Indriyawati; Ritzkal; Ade Hendri Hendrawan (Institute of Computer Science (IOCS), 2022)
Routing determines the route or path taken by packets and flows from sender to receiver. Software Define Networking (SDN) is a new concept for designing, building, and managing computer networks by separating controllers and devices. However, the development of a network that is currently increasing makes a computer network require a decision support mechanism, especially in determining the route or path taken by packets and flows from sender to receiver. This study aims to make a routing decision recommendation system using the Naïve Bayes algorithm using a QoS dataset including throughput, packet loss, delay, and jitter with Tiphon standards and QoS requirements for several applications on the network. Openflow protocol, Ryu controller, and simulation-based implementation using mininet were used in this study. The performance results show that the Naive Bayes algorithm can provide routing recommendations for www Browsing, Video Streaming HD, and VoIP Telephony applications with an accuracy of 91% and an average precision of 95%.